Host- rather than virus-related factors reduce health-related quality of life in hepatitis C virus infection. Issue 11 (14th July 2008) - Helbling, B; Overbeck, K; Gonvers, J-J; Malinverni, R; Dufour, J-F; Borovicka, J; Heim, M; Cerny, A; Negro, F; Bucher, S; Rickenbach, M; Renner, E L; et al.
Abstract : Background: Hepatitis C virus (HCV) infection is associated with decreased health-related quality of life (HRQOL). Although HCV has been suggested to directly impair neuropsychiatric functions, other factors may also play a role. Patients and methods: In this cross-sectional study, we assessed the impact of various host-, disease- and virus-related factors on HRQOL in a large, unselected population of anti-HCV-positive subjects. All individuals (n = 1736) enrolled in the Swiss Hepatitis C Cohort Study (SCCS) were asked to complete the Short Form 36 (SF-36) and the Hospital Anxiety Depression Scale (HADS). Results: 833 patients (48%) returned the questionnaires. Survey participants had significantly worse scores in both assessment instruments when compared to a general population. By multivariable analysis, reduced HRQOL (mental and physical summary scores of SF-36) was independently associated with income. In addition, a low physical summary score was associated with age and diabetes, whereas a low mental summary score was associated with intravenous drug use. HADS anxiety and depression scores were independently associated with income and intravenous drug use. In addition, HADS depression score was associated with diabetes. None of the SF-36 or HADS scores correlated with either the presence or the level of serum HCV RNA. In particular, SF-36 and HADS scores were comparable in 555 HCV RNA-positive and 262 HCV RNA-negative individuals. Conclusions: Anti-HCV-positive subjects have decreased HRQOL compared to controls. The magnitude of this decrease was clinically important for the SF-36 vitality score. Host and environmental, rather than viral factors, seem to impact on HRQOL level.